Co-operative Banks - A Helping Hands for Small and Medium Entrepreneurs in Saharanpur District - Nisha; Rani, Rekha (Integrated Journal for Research in Arts and Humanities, 2024)
Co-operative banks are more structured compared to credit associations. While local branches of cooperative banks can pick their own leaders and manage their own tasks, big decisions need to be approved by a main office. Credit associations frequently exercise significant local fundamental leadership, but by joining forces, they can share back-office functions including access to the global payments system. This essay provides background information on cooperative banks and small bank groups. Co-operative banks have more information available than "little establishments" as a whole cooperative banking systems exhibit greater organizational structure compared to credit association systems. Local branches of cooperative banks have autonomy in selecting their executive candidates and managing their operations. Small and medium enterprises (SMEs) encounter unique challenges in their development compared to large enterprises. The competitive market environment demands that SMEs adapt to the survival-of-the-fittest dynamics inherent in a market economy. In essence, this translates to a competition for human resources, making staff training a crucial method for SMEs aiming at long-term, stable development. Staff training serves as a fundamental approach to elevate the quality of human resources within SMEs. The paper provides background information on cooperative banks and small bank groups, highlighting their organizational structure and decision-making processes. It emphasizes the importance of staff training in small and medium enterprises (SMEs) for long-term, stable development, as it enhances the quality of human resources and improves overall productivity and competitiveness. The paper discusses the role of corporate culture in SMEs, stating that cultivating a positive corporate culture can enhance cohesion, employee loyalty, motivation, and job satisfaction, ultimately fostering productivity and innovative outcomes. It also highlights that a strong corporate culture can be a unique selling proposition for SMEs in attracting and retaining top talent. Additionally, the paper mentions the significance of cooperative banks in rural financing and their growing activity in metropolitan areas, contributing to the local economy and employment generation.